Parapagus Conjoined Twin Calf: A Case Study – Focused on CT and Cardiac Abnormalities. (3rd June 2013) - Schneevoigt, J.; Bahramsoltani, M.; Gerlach, K.; Gericke, A.; Fersterra, M.; Brehm, W.; Seeger, J.
Summary Congenital duplication anomalies occasionally occur in both humans and animals. Although various forms of classification of these conjoined twins exist, each case should be considered as an individual. In the case study presented a Holstein Frisian calf, born alive after 281 days of normal gravidity was investigated by computed tomography (CT) and subsequent dissection. The calf could be classified as a parapagus dicephalus tetrabrachius. It exhibited two heads each of them with a complete cervical spine leading to a complete thoracic and lumbar spine and separate tails. Looking at the point of fusion, the twin was conjoined in the ventrolateral thoracic part of the body. The calf had two thoraces with four forelimbs and two pelvic limbs on a single pelvis. As two heads and thoraces were present, beginning at the oral cavity, two intestinal systems were observable leading to a fusion point at the ascending part of the duodenum been continued caudally as a single system. Within each thorax, two lungs and a heart were present. However, only the heart in the left thorax was normal shape, exhibiting a strong myocardium and increased size. In contrast, the heart within the right thorax was considerably smaller, round shaped, and it appeared to be spongy and not fully developed during the foetal period. Commonly, classification of conjoined twins is only based on the appearance of the skeletal system. However, in the case presented, the point of fusion of the skeletal system did not allow conclusions regarding the intestinal or cardiovascular system.